Relação entre responsabilidade social, percepção do valor de marca e confiança sob a ótica do consumidor - Cavalcante, Fernanda Matte (Universidade do Vale do Rio dos Sinos, 2011)
Corporate Social Responsibility – CSR from the 90’s is playing a more active role in society, which reflects the growth in the study are a in recent years. Still a little investigated topic, this paper aims to provide and develop the subject in order to identify possible influences of CSR on consumers. This dissertation investigates the relationship of CSR together with the consumer confidence variables and brand value. Search – to deepen the understanding of the relationships between these items and the customer. where survey respondents were individual clients Banrisul. Were proposed theoretical models and research the field to support the hypotheses suggested. Through exploratory and descriptive research, carried out a survey of approximately 150 customers Banrisul. As general results, we verified the relationship of CSR in the bank’s clients. Other results and implications of the study were also discussed. It was concluded thatCSR relates to brand value, mediated by the variable trust. Banrisul customers consider important the role of the institution in the social sector, but virtually unaware of the social programs developed by the bank.n
Keywords: Responsabilidade social empresarial; Confiança; Valor de marca; Banrisul; Corporate social responsibility; Trust; Value brand; ACCNPQ::Ciências Sociais Aplicadas::Administração